Breastfall and Sexual Journey - Eliassen Seifert, Natalie (Taideyliopiston Kuvataideakatemia, 2023)
During the graduation show Kuvan Kevät 2022, I exhibited a three-screened video Installation Sexual Journey Interviews and a sculptural installation Breastafall. Brestfall was a result of a one-month casting performance, where I moulded and casted 30 breasts of voluntary people that had signed up. All genders were welcome to donate their breasts in a private casting session. The models were choosing the colours and glitter I would paint their plaster breast sculpture with. When the sculpture was ready, I found a place for it in the artificial waterfall. The volunteers got their sculpture copies of their breasts back after the exhibition. The waterfall ended in a hexagon-shaped pool with a breast fountain in glazed ceramic. The construction, of wood and black plastic, contained a mix of plaster breasts, ceramic breasts, ceramic support pieces, water, and oysters’ seashells. Brestfall is a celebration of breast diversity and is based on my curiosity about nudity. During Kuvan Kevät was Brestfall installed on the last steps of the stairs at the main entrance of the Academy of Fine Arts Helsinki, during the casting performance it was installed in the Kuva/Tila gallery. Sexual Journey Interviews presents a soundtrack with 12 personal histories about sexuality with kaleidoscopic visuals, on three TVs and seven headphones, in the Kuva-hall on the second floor. Under each TV screen was a wood sign with keywords from the interviews. The keywords from the three videos were: A: Relationship, Nudity, Squirting, Drag, Body image, Asexual, Identity, Love. B: Lovers, Dominant/Submissive, Dating, Boundaries, Chasing, Communicating, Pain. C: Spiritual, Orgasm, Motherhood, Porn, Gaze, Masturbation Club, Desire. I wanted to learn more about my own sexuality by hearing new perspectives from others of my same generation. The interviews were mostly conducted live in a sound studio at the academy, but some were recorded online. They often lasted for an hour, from which I made about 12 min excerpts. In both my works, the individuals who contributed remained anonymous in the exhibition, but since the subject in the interviews were using their own voices, they could be recognized. The written component is describing the whole process of making my two works about nudity and sexuality. From my first ideas, the actual working process with materials and techniques, a work description of how it was presented, and thoughts and knowledge I gained after the exhibition. Inspiring artists, elaborating on keywords from the videos, science about sexuality and clitoris, and concepts such as the “sexual script” and “the male gaze” are woven throughout the text. In my art, I’m interested in investigating, exploring, and describing human sexuality. I wish to take part in creating a healthier culture around sex by encouraging people to think and talk more openly about their experiences and wishes. In my practical works, I chose to focus on all different genders, this is contrary to that several parts of this master text are written from my female perspective. I have just started the journey of unlearning to read the word through binary contrast thinking. Most matters are more than two-sided, instead, they are floating in kaleidoscopic angels and shapes.
Keywords: seksuaalisuus; kuvataide; seksuaalinen käyttäytyminen; tilataide; identiteetti; taiteilijat; parisuhde; seksologia; sexuality (sexual orientation); breasts; ceramic art; installation; video art; sculpture (visual arts); fi=tila-aikataiteet|sv=tid- och rumkonst|en=Time and Space Arts|